The impact of perioperative red blood cell transfusions in patients undergoing liver resection: a systematic review protocol. Issue 1 (December 2016) - Bennett, Sean; Baker, Laura; Shorr, Risa; Martel, Guillaume; Fergusson, Dean
Abstract Background Liver resection is commonly performed for malignant and benign disease and is associated with frequent use of intraoperative and postoperative blood transfusions. Blood transfusions are potentially life-saving, but they have many adverse effects; some well understood, and others less so. Some of the poorly understood side effects include increased risk of postoperative complications and possibly worse oncologic outcomes. The objective of this systematic review is to provide estimates of transfusion prevalence and the effects of perioperative blood transfusion on postoperative mortality and morbidity and long-term cancer outcomes in patients undergoing liver resection. Methods/design The Cochrane, Medline, and EMBASE databases will be searched for any randomized controlled trial or observational cohort study comparing liver resection patients that received intraoperative or postoperative allogeneic red blood cell transfusions to those who did not. Outcomes include postoperative mortality, postoperative morbidity (infectious, liver failure, renal failure, cardiovascular/cerebrovascular events, and thromboembolic events), and long-term disease-free and overall survival. Only studies with adult, human patients (>18 years old) undergoing liver resection, in which the primary intervention of interest is blood transfusion will be included. Data will be extracted by two reviewers in duplicate and synthesized into a narrative review. Risk of bias will be assessed. When clinically and methodologically appropriate, meta-analysis will be performed. Discussion Our review will synthesize the literature pertaining to the potential beneficial and detrimental effects of red blood cell transfusion in patients undergoing liver resection. It will be an important step in the development of guidelines for the appropriate use of blood transfusions in patients undergoing liver resection. Systematic review registration PROSPERO CRD42015026132